US Medical Trainees' Knowledge of Human Papilloma Virus and Head and Neck Cancer. (29th October 2019) - Laitman, Benjamin M.; Ronner, Lukas; Oliver, Kristin; Genden, Eric
Abstract : Given the increasing incidence of human papilloma virus (HPV)–positive head and neck cancers (HNCs), discussion of this oncologic outcome should be incorporated into HPV vaccine counseling practices. Yet, preliminary evidence shows that knowledge of the association between HPV and HNC is lacking among most medical trainees. To better characterize this deficit, we nationally assessed knowledge of HPV's association with HNC among medical students and residents across 4 specialties (pediatrics, obstetrics and gynecology, family medicine, and otolaryngology). A total of 3141 responses from 46 states were obtained (n = 402 pediatric residents, n = 346 obstetrics/gynecology residents, n = 260 family medicine residents, n = 87 otolaryngology residents, and n = 2045 medical students). Only 40.3% of surveyed medical students and 56.1% of surveyed obstetrics/gynecology, pediatrics, and family medicine residents identified associations between persistent HPV infection and HNC. When counseling on the vaccine, nonotolaryngology residents more often discussed cervical cancer (99.8%) as compared with HNC (39.7%), commonly because of less HNC knowledge (61.5%). These results suggest that it is imperative to develop educational interventions targeted at medical students and resident trainees on the front line of HPV vaccine counseling and administration.